EXPLORING THE EFFECTIVENESS OF THE BASIC CHEMISTRY LESSONAPPROACH: ANALYSIS OF PERCEPTIONS AND IMPACT ON ENTRANCE TO STATE UNIVERSITIES - Permata Fonna (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
The study investigated the effectiveness of the Basic Chemistry Lesson Approach at State High School 5 Banda Aceh and its influence on students' perceptions and entrance to state universities. A mixed-methods research design collected and analyzed quantitative data regarding students' academic performance and qualitative data on their perceptions. The findings revealed that the Basic Chemistry Lesson Approach significantly enhanced students' understanding of chemistry concepts and positively impacted their performance in university entrance exams. Moreover, qualitative analysis demonstrated that students perceived the approach as engaging and beneficial to their learning experiences. The study highlighted the importance of innovative teaching methodologies in improving students' academic achievements and shaping their educational trajectories. The implications of these findings extended to educators, policymakers, and educational stakeholders, emphasizing the value of evidence- based instructional practices in enhancing learning outcomes in chemistry education.